Maximum Power Point Tracking in PV Arrays with High Gain DC-DC Boost Converter - Arsyad Cahya Subrata; Tole Sutikno; Sanjeevikumar Padmanaban; Hendril Satrian Purnama (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
Photovoltaic (PV) system is an electricalgenerator that has been widely used. Ease of implementation,supported by a large number of potentials and needs of GreenEnergy, has become a factor in the increasing number andquickly applied to PV arrays. However, PV arrays haveconstrained related to generator conversion efficiency and theamount of power produced due to inconstant irradiation andtemperature. This problem can be solved by a MaximumPower Point Tracking (MPPT) approach. This article discussesthe MPPT technique with High Gain DC-DC Boost Converterusing the Perturb and Observe (P&O) algorithm. The sameP&O algorithm is also tested in the conventional converter toshow performance and superiority of each converter. Theresults obtained show the advantages and disadvantages ofeach converter used in MPPT by P&O algorithm.